2007
DOI: 10.1002/env.849
|View full text |Cite
|
Sign up to set email alerts
|

The generalized linear model and extensions: a review and some biological and environmental applications

Abstract: SUMMARYThe generalized linear model (GLM) encompasses many discrete and continuous models and it is particularly useful for analyzing discrete data. However, in many real life applications, the full distributional assumption of the GLM cannot be justified. Further, the GLM cannot accommodate over-dispersion in the data. Since the inception of the GLM by Nelder and Wedderburn (1972) a number of its extensions have been proposed in the literature for robust analysis of discrete data. The purpose of this paper is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Increased induction of micronuclei in PUBEC by increased 4-ABP concentrations without and in combination with 1 M B[a]P was investigated using a quasi-binomial model with the log link function accounting for overdispersion and variation between PUBEC (Paul and Saha 2007). Williams-type contrasts (Williams 1971) were used to detect a possible concentrations-related trend supposing a monotone trend for increasing 4-ABP concentrations, 1 M B[a]P without 4-ABP, and combinations of 1 M B[a]P and increasing 4-ABP concentrations (Hothorn et al 2008;Hothorn and Gerhard 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Increased induction of micronuclei in PUBEC by increased 4-ABP concentrations without and in combination with 1 M B[a]P was investigated using a quasi-binomial model with the log link function accounting for overdispersion and variation between PUBEC (Paul and Saha 2007). Williams-type contrasts (Williams 1971) were used to detect a possible concentrations-related trend supposing a monotone trend for increasing 4-ABP concentrations, 1 M B[a]P without 4-ABP, and combinations of 1 M B[a]P and increasing 4-ABP concentrations (Hothorn et al 2008;Hothorn and Gerhard 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the variability between dishes can be well taken into account by a quasi-Poisson model developed for counts, where a dispersion parameter is estimated from the complete data [16]. This led to the agreement that a negative binomial generalised linear model (i.e.…”
Section: Recommended Statistical Data Analysismentioning
confidence: 82%
“…In the hierarchical generalized linear model setup, Lee and Nelder 29 propose the DEQL to estimate the mean and the dispersion parameters of the response variable. Omitting the detailed derivation here, we obtain the profile DEQL from Paul and Saha 16, apart from a constant, as The maximum DEQL estimates of µ and a are then obtained by maximizing D + , or, alternatively, by solving the estimating equations and simultaneously. Denote the DEQL estimate of a by .…”
Section: The Point Estimation Of Amentioning
confidence: 99%
“…For example, it is commonly used as an inverse measure of aggregation in biological count data 2, 6–12. Extensive work has been done on its point estimation in terms of bias and efficiency 13–17 and testing for over‐dispersion 18–21. However, little has been done on the construction of confidence intervals (CIs) of the over‐dispersion parameter.…”
Section: Introductionmentioning
confidence: 99%